Upaya Melaksanakan Fungsi Monitoring Kepengawasan Membantu Kepala Madrasah Dan Guru Dalam Pengelolaan Pembelajaran Pada Madrasah Binaan - Mohammad Sadik B (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2023)
Abstract Monitoring as an approach technique in developing teacher learning is a pattern based on the basic assumption that the teacher's learning process to develop in his position cannot be separated from the learning process carried out by the teacher. Learning is individual, therefore, the socialization process must be carried out by helping teachers face to face and individually. Monitoring as a technique has certain steps that need attention to develop the professionalism of the madrasa head and teachers. The madrasa supervisor who serves as a supervisor only has to manage and allocate programmed time between the madrasa supervisor as a supervisor and the teacher as a person who needs guidance. This activity will actually have a significant impact on both parties. Teachers feel helped by the guidance of the madrasa supervisor, while the madrasa supervisor will benefit in the form of improving the quality of learning that exists for each madrasa head and teacher. Keywords: Monitoring Function, Learning Management